2015
DOI: 10.7314/apjcp.2015.16.1.315
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Spontaneously Ruptured Hepatocellular Carcinoma Benefit from Staged Surgical Resection after Successful Transarterial Embolization

Abstract: Background: Surgical resection of spontaneously ruptured hepatocellular carcinoma (HCC) after successful transarterial embolization (TAE) remains controversial. The aim of this study was to investigate its efficacy in a series of cases. Materials and Methods: We retrospectively examined ruptured HCC cases from Jan 2000 to Dec 2008; all of these 126 cases received TAE as the initial therapy. Subsequently, 74 cases received staged surgical resection, and the remaining 52 cases underwent repeated TACE. The baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Searching the reference list (snowball procedure) retrieved two additional articles. In total, 67 studies were deemed eligible and therefore included in the systematic review …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Searching the reference list (snowball procedure) retrieved two additional articles. In total, 67 studies were deemed eligible and therefore included in the systematic review …”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the study population was 55.6 years (SD = 6.64) with most patients being male (77.9%). A large portion of the cohort population consisted of patients from Asia, as 22 studies (33%) were from China, 17 (25%) from Japan, 10 (15%) from Taiwan, 5 (7.5%) from Korea, 2 (3%) from Thailand, and 1 (1.5%) each from Singapore and Malaysia . In contrast, studies about rHCC were less common from Western centers with only 2 reports (3%) from the Netherlands and Italy, and 1 (1.5%) each from Canada, France, United Kingdom, USA, and Nigeria .…”
Section: Resultsmentioning
confidence: 99%
“…Once initial hemostasis after active supporting therapy is achieved, the patient will have a chance to undergo a staged hepatectomy. There are many clinical reports [8,18,19] that the therapeutic effect on staged hepatectomies after TAE hemostasis can be comparable to those procedures with these kinds of elective liver resection on non-ruptured HCC patients. This is also the best and most radical approach for patients with HCC ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [29] reported an 11.8% incidence of peritoneal disease in their series of ruptured HCCs. In the present study, there was an 11% peritoneal recurrence rate in the emergency hepatectomy group compared to 29% in the interval hepatectomy group (P = 0.27).…”
mentioning
confidence: 97%
“…Zhang et al [29] reported on the impact of interval hepatectomy or repeat TACE after successful TACE for ruptured HCC. One hundred and twenty-six cases of ruptured HCC underwent TAE for haemostasis of which 74 had interval hepatectomy.…”
mentioning
confidence: 99%